Two Cases of Mixed Medullary and Follicular Cell Carcinoma with Literature Review - Guo, Yekun; Qin, Zuorong; Qiu, Jie; Xu, Zhenju; Shen, Bingying; Zhang, Wenwei (ENT Updates, 2026)
Mixed Medullary and Follicular Cell Carcinoma (MMFCC) is a rare thyroid cancer combining medullary and follicular (often papillary) elements. The lack of standard clinical signs and imaging characteristics makes it difficult to diagnose before surgery. At present, the main approach to treatment is surgical removal, and the outlook for patients is primarily influenced by how advanced the medullary carcinoma is. We report two cases of MMFCC confirmed by postoperative pathology. Case 1 involved a 46-year-old woman with bilateral thyroid nodules and left cervical lymph node metastasis. Preoperative ultrasound classified the nodules as TI-RADS 4c, and fine-needle aspiration cytology suggested papillary thyroid carcinoma. Total thyroidectomy with bilateral neck lymph node dissection was performed. Postoperative pathology revealed MMFCC, with a medullary component accounting for approximately 95% and extensive lymph node metastasis. Six weeks postoperatively, serum calcitonin was 73.00 pg/mL. Case 2 involved a 54-year-old man presenting with neck pain. Ultrasound showed a hypoechoic left thyroid nodule (TI-RADS 4b) with bilateral cervical lymphadenopathy. Fine-needle aspiration suggested medullary thyroid carcinoma, and serum calcitonin and carcinoembryonic antigen levels were markedly elevated. Following total thyroidectomy with bilateral neck lymph node dissection, pathology confirmed MMFCC with an approximately 80% medullary component. Postoperative tumor markers decreased significantly, and long-term follow-up was initiated. MMFCC is a rare thyroid carcinoma with considerable diagnostic difficulty. Fine-needle aspiration alone may be insufficient for accurate diagnosis, whereas preoperative serum calcitonin testing provides important diagnostic clues. Total thyroidectomy with systematic lymph node dissection is advised, plus long-term monitoring per both carcinoma guidelines.